THE ANNUAL WELLNESS VISIT: WHAT IT IS AND HOW IT CAN BE DONE IN PRIMARY CARE. (11th November 2018) - Resnick, B
Abstract: The Annual Wellness Visit (AWV) includes a health risk assessment and customized wellness or personal prevention plan for Medicare beneficiaries. Within a Continuing Care Retirement Community, AWVs are done during the birthday month of the resident and include basic assessments, cognitive screening, the PHQ-2, review of smoking, alcohol use, driving status, a functional assessment, review of medications, physical activity, screening for cardiovascular risks, cancer screenings, medications and advanced directives. Behavior change interventions are implemented using social cognitive theory. Outcomes associated with AWV include 100% adherence to completion of advanced directives, decreased number of inappropriate cancer screenings, increased physical activity, and increased management of mental health issues. The AWV allows for a focused review of critically important health issues for older adults prior to an acute event occurring such as a motor vehicle accident or an acute delirium and ideally can help to decrease the time spent disabled among older adults.